2019
DOI: 10.1177/1120700019874822
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cup placement in total hip arthroplasty by means of a mechanical positioning device: a comprehensive cadaveric 3d analysis of 16 specimens

Abstract: Introduction: We tested whether a mechanical device (such as Hipsecure) to pinpoint the anterior pelvic plane (APP) as a guide can improve acetabular cup placement. To assess accuracy we asked: (1) is the APP an effective guide to position acetabular cup placement within acceptable ° of divergence from the optimal 40° inclination and 15° anteversion; (2) could a mechanical device increase the number of acetabular cup placements within Lewinnek’s safe zone (i.e. inclination 30° to 50°; anteversion 5° to 25°)? M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…More complex mechanical devices using anterior pelvic plane have been tested in cadavers. 15 They also found it helpful to increase the accuracy in positioning of the acetabular cup, but uses of such devices have their own drawbacks like increased surgery time and complications associated with reference pin placement. Similarly MRIbased patient-specific instrumentation guide have been used during THA.…”
Section: Discussionmentioning
confidence: 99%
“…More complex mechanical devices using anterior pelvic plane have been tested in cadavers. 15 They also found it helpful to increase the accuracy in positioning of the acetabular cup, but uses of such devices have their own drawbacks like increased surgery time and complications associated with reference pin placement. Similarly MRIbased patient-specific instrumentation guide have been used during THA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the popularity of this technique has decreased due to its complexity and increase in operation time. A mechanical device pinpointing the anterior pelvic plane to optimize acetabular component placement was developed by Kievit et al, who found that it improved positioning with respect to the Lewinnek’s safe zones; however, this device has not been proven to work in the clinical setting [ 15 ]. Perioperative imageless techniques use infrared optical stereoscopy that allows for three-dimensional tracking of the prosthetic components and tools.…”
Section: Introductionmentioning
confidence: 99%